2020
DOI: 10.18775/ijied.1849-7551-7020.2015.61.2005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Economic Uncertainty on Mental Health in the COVID-19 Pandemic Context: Social Identity Disturbance, Job Uncertainty and Psychological Well-Being Model

Abstract: Psychological well-being is a major global concern receiving more scholarly attention following the 2008 Great Recession, and it becomes even more relevant in the context of COVID-19 outbreak. In this study, we investigated the impact of economic uncertainty resulting from natural disasters, epidemics, and financial crisis on individuals’ mental health. As unemployment rate exponentially increases, individuals are faced with health and economic concerns. Not all society members are affected to the same extent,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
201
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(223 citation statements)
references
References 4 publications
15
201
0
7
Order By: Relevance
“…Retrospective research indicates a strong link between nancial solvency and good mental well-being [20]. Similar to our results, a report found that business and career uncertainty have a substantial adverse effect on the mental health of the adult population [21].…”
Section: Discussionsupporting
confidence: 90%
“…Retrospective research indicates a strong link between nancial solvency and good mental well-being [20]. Similar to our results, a report found that business and career uncertainty have a substantial adverse effect on the mental health of the adult population [21].…”
Section: Discussionsupporting
confidence: 90%
“…Regarding our main hypotheses, we found support for the association between perceived job insecurity and depressive symptoms, as well as for the moderating role of a fear of being infected by COVID-19 in this relationship. The relationship between perceived job insecurity and negative mental health outcomes is well established in literature [14][15][16][17][18] and might be explained by virtue of the fact that pandemics (e.g., the COVID-19 outbreak) may produce a great uncertainty about the future [39] and even about one's own job, thus causing a temporary economic uncertainty. Indeed, although not directly assessed in the current study, it is plausible to hypothesize that many factors (e.g., the severity of the lockdown measures, the severe containment measures adopted by governments to reduce the risk of contagion within healthcare contexts, the regional economic conditions, the perceptions of alternative work, or the client portfolio of the dentists) may have affected the dentists' perception of job insecurity, creating a strong economic uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, although not directly assessed in the current study, it is plausible to hypothesize that many factors (e.g., the severity of the lockdown measures, the severe containment measures adopted by governments to reduce the risk of contagion within healthcare contexts, the regional economic conditions, the perceptions of alternative work, or the client portfolio of the dentists) may have affected the dentists' perception of job insecurity, creating a strong economic uncertainty. As a consequence, such an economic uncertainty, together with the uncertainty about one's own job and the future in general, may have produced in turn severe psychopathological conditions, such as depressive symptoms [39]. Based on our results, this seems particularly significant with respect to older workers, who have a lower level of perceived occupational mobility and a greater sensitivity to economic insecurity than their younger counterparts [14], and with respect to those who have a personal knowledge of people who have died due to COVID-19, as mourning may exacerbate depressive feelings.…”
Section: Discussionmentioning
confidence: 99%
“…Plohl and Musil (2020) explored why people deliberately disregard or ignore the health measures imposed during the current pandemic, suggesting that the perception of the SARS-CoV-2 risk and trust in science might predict people's compliance with the general prevention guidelines. The current situation is highly unpredictable regarding the pandemic's health, economic, social, and psychological consequences (Godinic et al, 2020). Therefore, the variations in people's SARS-CoV-2 risk estimates and consequent cautiousness and compliance might be partly explained by their general cognitive and emotional approach to uncertainty.…”
Section: Introductionmentioning
confidence: 99%